A Novel Platelet Concentrate: Titanium-Prepared Platelet-Rich Fibrin. (20th January 2014) - Tunalı, Mustafa; Özdemir, Hakan; Küçükodacı, Zafer; Akman, Serhan; Yaprak, Emre; Toker, Hülya; Fıratlı, Erhan
Abstract : We developed a new product called titanium-prepared platelet-rich fibrin (T-PRF). The T-PRF method is based on the hypothesis that titanium may be more effective in activating platelets than the silica activators used with glass tubes in Chouckroun's leukocyte- and platelet-rich fibrin (L-PRF) method. In this study, we aimed to define the structural characteristics of T-PRF and compare it with L-PRF. Blood samples were collected from 10 healthy male volunteers. The blood samples were drawn using a syringe. Nine milliliters was transferred to a dry glass tube, and 9 mL was transferred to a titanium tube. Half of each clot (i.e., the blood that was clotted using T-PRF or L-PRF) was processed with a scanning electron microscope (SEM). The other half of each clot was processed for fluorescence microscopy analysis and light microscopy analysis. The T-PRF samples seemed to have a highly organized network with continuous integrity compared to the other L-PRF samples. Histomorphometric analysis showed that T-PRF fibrin network covers larger area than L-PRF fibrin network; also fibrin seemed thicker in the T-PRF samples. This is the first human study to define T-PRF as an autogenous leukocyte- and platelet-rich fibrin product. The platelet activation by titanium seems to offer some high characteristics to T-PRF.